Comparative Analyses of Cu-Zn Superoxide Dismutase (SOD1) and Thioredoxin Reductase (TrxR) at the mRNA Level between Apis mellifera L. and Apis cerana F. (Hymenoptera: Apidae) Under Stress Conditions. Issue 1 (21st January 2016) - Koo, Hyun-Na; Lee, Soon-Gyu; Yun, Seung-Hwan; Kim, Hyun Kyung; Choi, Yong Soo; Kim, Gil-Hah
Abstract: This study compared stress-induced expression of Cu-Zn superoxide dismutase (SOD1) and thioredoxin reductase (TrxR) genes in the European honeybee Apis mellifera L. and Asian honeybee Apis cerana F. Expression of both SOD1 and TrxR rapidly increased up to 5 h after exposure to cold (4°C) or heat (37°C) treatment and then gradually decreased, with a stronger effect induced by cold stress in A. mellifera compared with A. cerana . Injection of stress-inducing substances (methyl viologen, [MV] and H2 O2 ) also increased SOD1 and TrxR expression in both A. mellifera and A. cerana, and this effect was more pronounced with MV than H2 O2 . Additionally, we heterologously expressed the A. mellifera and A. cerana SOD1 and TrxR proteins in an Escherichia coli expression system, and detection by SDS-PAGE, confirmed by Western blotting using anti-His tag antibodies, revealed bands at 16 and 60 kDa, respectively. Our results show that the expression patterns of SOD1 and TrxR differ between A. mellifera and A. cerana under conditions of low or high temperature as well as oxidative stress.